Repeated sprint training improves both anaerobic and aerobic fitness in basketball players - Gantois, P.; Batista, G. R.; Aidar, F. J.; Nakamura, F. Y.; de Lima-Júnior, D.; Cirilo-Sousa, M. S.; de Matos, D. G.; Cabral, B. G. A. T. (Isokinetics and Exercise Science, 2019)
BACKGROUND: Basketball is an intermittent sport were both neuromuscular and aerobic fitness are essential for the players. Thereby, repeated sprint training seems to be a feasible training strategy to improve these physical attributes. OBJECTIVE: The aim of the present study is to verify the effect of repeated sprint training on the anaerobic and aerobic performance in basketball players. METHODS: Seventeen college players were randomized into two groups, repeated sprint training (n = 9) and control group (n = 8). The repeated sprint training group performed 2-3 sets of 6 × 30 m all-out sprints, twice per week, in addition to the regular training routine. The control group performed only regular training routine during six weeks on the pre-season. The dependent variables were aerobic fitness, vertical countermovement jump, repeated vertical jump ability, and repeated sprints ability. RESULTS: Repeated sprint training improve the best sprint time (p = 0.033), worst sprint time (p = 0.035), sprint decrement (p = 0.04), CMJ (p = 0.037), and peak speed in the incremental test (p = 0.008). CONCLUSION: Repeated sprint training is effective in conditioning neuromuscular quality-related abilities of short sprint speed, jump, and aerobic fitness in college basketball players during the last phase of the pre-season.